SAXS analysis of the tRNA-modifying enzyme complex MnmE/MnmG reveals a novel interaction mode and GTP-induced oligomerization. Issue 9 (14th March 2014) - Fislage, Marcus; Brosens, Elke; Deyaert, Egon; Spilotros, Alessandro; Pardon, Els; Loris, Remy; Steyaert, Jan; Garcia-Pino, Abel; Versées, Wim
Abstract: Transfer ribonucleic acid (tRNA) modifications, especially at the wobble position, are crucial for proper and efficient protein translation. MnmE and MnmG form a protein complex that is implicated in the carboxymethylaminomethyl modification of wobble uridine (cmnm 5 U34) of certain tRNAs. MnmE is a G protein activated by dimerization (GAD), and active guanosine-5'-triphosphate (GTP) hydrolysis is required for the tRNA modification to occur. Although crystal structures of MnmE and MnmG are available, the structure of the MnmE/MnmG complex (MnmEG) and the nature of the nucleotide-induced conformational changes and their relevance for the tRNA modification reaction remain unknown. In this study, we mainly used small-angle X-ray scattering to characterize these conformational changes in solution and to unravel the mode of interaction between MnmE, MnmG and tRNA. In the nucleotide-free state MnmE and MnmG form an unanticipated asymmetric α2β2 complex. Unexpectedly, GTP binding promotes further oligomerization of the MnmEG complex leading to an α4β2 complex. The transition from the α2β2 to the α4β2 complex is fast, reversible and coupled to GTP binding and hydrolysis. We propose a model in which the nucleotide-induced changes in conformation and oligomerization of MnmEG form an integral part of the tRNA modification reaction cycle.